ADSORPSI KATION Pb(II) DAN Cr(III) OLEH BATU PADAS JENIS LADGESTONE TERAKTIVASI H2SO4 DAN NaOH - Novita Rambu Atandawu; Ida Ayu Gede Widihati; I Wayan Suarsa (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2013)
Adsorption of Pb (II) and Cr (III) cations by ladgestone activated with 2 N sulfuric acid, and 4 N sodium hydroxide have been studied. The activation aims to increase the adsorption capacity of the ladgestone which was characterized by measuring its specific surface area and the acidity of the ladgestone surface. In addition, equilibrium adsorption time, isotherm adsorption, and the adsorption capacity were also determined using atomic absorption spectrophotometry (AAS). The results showed that activation with 2 N sulfuric acid increased the acidity of ladgestone surface but it decreased the specific surface area, while activation with 4 N sodium hydroxide increased both the acidity and the specific surface area of the ladgestone. Hence, ladgestone activated with 4 N sodium hydroxide gave the highest adsorption capacity both for Pb (II) and Cr (III) which were 12.4976 mg/g and 12.4945 mg/g respectively.